Cotton varieties for the state of Minas Gerais - Fallieri, Joel; Silva, Arnaldo F. da; Castro, Celso Soares de; Souza, José Alípio de; Cardoso, José Luís; Molica, Vicente de Paula; Costa, Eli Gaudêncio (Pesquisa Agropecuaria Brasileira, 2014)
Variety trials, using sixteen cultivars of cotton selected by the Instituto Agronômico de Campinas (IAC), São Paulo; the Instituto de Experimentação e Pesquisas Agropecuárias de Minas Gerais (IEPAP); and the Estação Experimental de Sete Lagoas (EESL), Minas Gerais were carried out in the four principal cotton - growing regions of the state of Minas Gerais: Montes Claros, Metalúrgica, Triângulo Mineiro, and Sul. The trials were repeated in three consecutive years. On the basis of the results of these trials and of quality determinations on the fibers of each of the cultivars studied, the following cultivars are recommended for the respective regions: 1) Montes Claros - IPEACO-SL 6; IAC 12-1; IAC 13; 2) Metalúrgica - IPEACO-SL 4; IPEACO-SL 6; IAC RM 4; 3) Triângulo Mineiro - IAC 13; IPEACO-SL 6; 4) Sul - IPEACO-SL 4; IAC 13; IAC RM 4.